Plastome mutations and recombination events in barley chloroplast mutator seedlings - Landau, Alejandra Mabel; Lencina, Franco; Pacheco, Maria Gabriela; Prina, Alberto Raul (2017)
The barley chloroplast mutator (cpm) is an allele of a nuclear gene that when homozygous induces several types of cytoplasmically inherited chlorophyll deficiencies. In this work, a plastome Targeting Induced Local Lesions in Genomes (TILLING) strategy based on mismatch digestion was used on families that carried the cpm genotype through many generations. Extensive scanning of 33 plastome genes and a few intergenic regions was conducted. Numerous polymorphisms were detected on both genic and intergenic regions. The detected polymorphisms can be accounted for by at least 61 independent mutational events. The vast majority of the polymorphisms originated in substitutions and small indels (insertions/deletions) in microsatellites. The rpl23 and the rps16 genes were the most polymorphic. Interestingly, the variation observed in the rpl23 gene consisted of several combinations of 5 different one nucleotide polymorphisms. Besides, 4 large indels that have direct repeats at both ends were also observed, which appear to be originated from recombinational events. The cpm mutation spectrum suggests that the CPM gene product is probably involved in plastome mismatch repair. The numerous subtle molecular changes that were localized in a wide range of plastome sites show the cpm as a valuable source of plastome variability for plant research and/or plant breeding. Moreover, the cpm mutant appears to be an interesting experimental material for investigating the mechanisms responsible for maintaining the stability of plant organelle DNA.